RUSSIAN EDUCATION AND INNOVATIONS: RETROSPECTIVE VIEW AND FORECAST - T. L. Likhachyova (Модернизация, инновация, развитие, 2016)
Starting from the Great Peter’s times, Russian education system passed many stages, each of the stages being characteristic with specificinnovations. Retrospective of these stages is discussed. Detailed analysis of the present situation in Russian education is given. Prospects of what may be expected for next ten years are discussed too.